The Attitudes of Primary Teacher Education Program Students Towards Utilizing Flipgrid in English Speaking Skill - Tri Wintolo Apoko; Su Li Chong (STKIP Singkawang, 2022)
This research was aimed at investigating the students’ attitudes of primary teacher education program (PTEP) towards utilizing Flipgrid in enhancing English speaking skill. The participants of this research were 60 students of PTEP in one of Muhammadiyah Universities located in Jakarta who attended an English course. The research used a mixed method to collect the quantitative and qualitative data to analyze. Thus, the instruments used were observation, questionnaire and semi-structure interview. The result showed that most of the students agreed to use Flipgrid in learning English speaking skill as this app had benefits and could motivate the students to practice speaking better as well as increased the students’ confidence. It is thus recommended that lecturers should be encouraged to use Flipgrid in English learning activity, mainly in speaking skill to boost the students to be more active to create videos and engage in interactions with lecturers and classmates mediated with video discussion forum.